(3cJGH aj GdJQGLes ((3eQGcT s)
(3ChdgG (B:s
(3GdeJhahf ef CYdGe GdeGFI GdKGefI hJhai ai CMO hSHYeGFI GdYGde CHh RcQjG jMji s
(3BNQgG (B:s
(3UGMHfG Gdabjg GdMGaX GdaMd GdNWjH CHh GdMSf Ydi Hf gGTe GdRbGb GfJgi eG hLOJ ebjOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs